Comparative Effect of Collaborative Care, Pain Medication, and Duloxetine in the Treatment of Major Depressive Disorder and Comorbid (Sub)Chronic Pain: Results of an Exploratory Randomized, Placebo-Controlled, Multicenter Trial (CC:PAINDIP) - de Heer, Eric W.; Dekker, Jack; Beekman, Aartjan T. F.; van Marwijk, Harm W. J.; Holwerda, Tjalling J.; Bet, Pierre M.; Roth, Joost; Timmerman, Lotte; van der Feltz-Cornelis, Christina M. (Frontiers in Psychiatry, 2018)
Objective: Evidence exists for the efficacy of collaborative care (CC) for major depression (MDD), for the efficacy of the consequent use of pain medication against pain, and for the efficacy of duloxetine against both MDD and neuropathic pain. Their relative effectiveness in comorbid MDD and pain has never been established so far. This study explores the effectiveness of CC with pain medication and duloxetine, and CC with pain medication and placebo, compared to duloxetine alone, on depressive and pain symptoms. This study was prematurely terminated because of massive reorganizations and reimbursement changes in mental health care in the Netherlands during the study period and is therefore of exploratory nature. Methods: Three-armed, randomized, multicentre, placebo-controlled trial at three specialized mental health outpatient clinics with patients who screened positive for MDD. Interventions lasted 12 weeks. Pain medication was administered according to an algorithm that avoids opiate prescription as much as possible, where paracetamol, COX inhibitors, and pregabalin are offered as steps before opiates are considered. Patients who did not show up for three or more sessions were registered as non-compliant. Explorative, intention-to-treat and per protocol, multilevel regression analyses were performed. The trial is listed in the trial registration (http://www.trialregister.nl/trialreg/admin/rctview.asp?TC=1089; NTR number: NTR1089). Results: Sixty patients completed the study. Patients in all treatment groups reported significantly less depressive and pain symptoms after 12 weeks. CC with placebo condition showed the fastest decrease in depressive symptoms compared to the duloxetine alone group (b = -.78; p = .01). Non-compliant patients (n=31) did not improve over the 12-week period, in contrast to compliant patients (n=29). Pain outcomes did not differ between the three groups. Conclusions: In MDD and pain, patient’s compliance and placebo effects are more important in attaining effect than choice of one of the treatments. Active pain management with COX inhibitors and Pregabalin as alternatives to Tramadol or other opiates might provide an attractive alternative to the current WHO pain ladder as it avoids opiate prescription as much as possible. The generalizability is limited due to the small sample size. Larger studies are needed.